Surface studies of centrifugally cast aluminum-based lead bearing composites - Mohan S.; Pathak J.P.; Chander N.; Sarkar S. (My University, 2025)
Low cost and abundant availability of aluminum-based composites make them potential candidates for bearing applications. The dispersion of lead is difficult in aluminum, so a centrifugal casting procedure has been adopted for uniform dispersion. Cylindrical castings show minor variation in composition from outer to inner as well as from top to bottom. Wear rate shows an increasing trend with sliding distance and load. But with sliding velocity wear rate initially decreases, attains a minimum, and then increases sharply with increase in sliding velocity. Under dry sliding conditions all alloys exhibit two regimes of wear, viz. mild wear at low loads and sliding velocities but severe wear at higher loads and sliding velocities. These two wear mechanisms are distinguished by a mixed mode of oxidative and metallic wear dominated by either. © SAGE Publications 2008.